2017
DOI: 10.1515/msr-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Analysis of Pressure, Noise and Vibration Velocity Measurement in Cavitation

Abstract: The article deals with experimental investigation of water cavitation in the convergent-divergent nozzle of rectangular cross-section. In practice, a quick and simple determination of cavitation is essential, especially if it is basic cavitation or cavitation generated additionally by the air being sucked. Air influences the formation, development and size of the cavity area in hydraulic elements. Removal or reduction of the cavity area is possible by structural changes of the element. In case of the cavitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…As the first step the digitization of the signals from the installed sensors was made [4]. Since the signal in the digital form has an electrical value, it was necessary to convert them to the values of the actual measured parameters.…”
Section: Design Methodsmentioning
confidence: 99%
“…As the first step the digitization of the signals from the installed sensors was made [4]. Since the signal in the digital form has an electrical value, it was necessary to convert them to the values of the actual measured parameters.…”
Section: Design Methodsmentioning
confidence: 99%
“…Jablonská et al. 36 measured the noise intensity and vibration velocity of a spatialized Venturi tube with and without air saturation, respectively. The results indicated that the added air can suppress the noise intensity.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous literature, Mancuso 35 conducted an experimental and numerical investigation on the performance of a swirling jet reactor with different geometric configurations and measured and analyzed the cavitation noise of different geometric shapes at different inlet pressures. Jablonskáet al 36 measured the noise intensity and vibration velocity of a spatialized Venturi tube with and without air saturation, respectively. The results indicated that the added air can suppress the noise intensity.…”
Section: Introductionmentioning
confidence: 99%
“…For future research, these extensive reference sources can be used for numerical modeling and experimental measurements of acoustic wave generation in the wind tunnel on actual car components. Methods of measuring and processing noise and vibrations and also numerical methods are also described in articles [16], [17], [18], [19].…”
Section: Introductionmentioning
confidence: 99%